Stres Akademik dan Respons Psikologis pada Mahasiswa di Masa Tekanan Akademik Tinggi: Studi Kualitatif - Ni Putu Artanti; Nyoman Intan Permatahati Wiguna; Ni Luh Putu Pranena Sastri (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Academic stress has become a significant psychological issue among university students, particularly during periods of high academic pressure such as examinations, intensive coursework, and academic performance demands. Excessive academic stress may negatively affect students’ psychological well-being, learning motivation, and academic performance. This study aims to explore in depth the experiences of academic stress and psychological responses among students during periods of high academic pressure. A qualitative descriptive approach with a phenomenological perspective was employed to capture students’ lived experiences. Data were collected through in-depth semi-structured interviews with six student participants selected using purposive sampling. The data were analyzed using thematic analysis, involving open, axial, and selective coding to identify emerging themes. The findings reveal that the main sources of academic stress include excessive academic workload, time management difficulties, high self-expectations, and external academic pressures. Students experienced varying levels of stress ranging from mild to severe, manifested through psychological responses such as anxiety, emotional instability, mental fatigue, decreased concentration, and reduced motivation. The study also found that students applied diverse coping strategies, including adaptive strategies such as time management, seeking social support, and self-reflection, as well as maladaptive strategies such as procrastination and emotional withdrawal. These findings highlight that academic stress is a complex and subjective experience influenced by individual perceptions and coping capacities. The study implies the importance of supportive academic environments and accessible mental health services in higher education institutions to promote students’ psychological well-being and resilience. The results may serve as a reference for developing preventive and promotive mental health programs for students facing academic stress..